Exploring the evolution of social cohesion: interdisciplinary theories and their impact - Sahharon, Hamizah; Bolong, Jusang; Omar, Siti Zobidah (Universiti Teknologi MARA, 2023)
Several scholars have studied the concept of social cohesion through several theories rooted in economics, sociology, anthropology, psychology, political science, and communication literature. Due to the advancement of human civilisation and economic growth, social cohesion is needed to understand the fundamental bond of human society because it can instil a more civilised state and civilised culture. This review aims to explain the evolution of social cohesion as a causal system that determines a persons membership attitudes and behaviours. Fourteen interrelated theories within sociology, psychology, and communication were identified to predict the nature of human society and explain the communicative processes or exchanges between individuals in a group or community to foster social cohesion. The theoretical evolution of social cohesion demonstrates a shift from focusing on group mechanisms to emphasising individual viewpoints, trust, and shared values as critical factors in fostering cohesion within modern society. This evolution, from Ibn Khaldun's group solidarity to Durkheim's collective consciousness, reflects the increasing complexity of contemporary society due to population growth. The transition to examining social cohesion at the individual level underscores the modern emphasis on personal beliefs for promoting loyalty and unity.